1987
DOI: 10.1128/jb.169.1.438-441.1987
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a substitution mutation in the ompR gene of Salmonella typhimurium LT2

Abstract: The expression of the genes ompC and ompF encoding major outer membrane proteins is dependent on the ompR-envZ operon. Here we describe the isolation and characterization of an ompR mutation, a single-base-pair change, that results in an Arg-to-Cys substitution. When present in multiple copies, the mutant allele conferred a dominant OmpC- OmpF+ phenotype. Furthermore, the mutant allele exhibited allele-specific negative complementation with other ompR mutations. This ability, together with its dominant charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The production of both OmpC and OmpF by serovar Typhimurium is dependent on envZ. A mutant derivative of LT2, SC2, with an envZ1005::Mud-P insertion makes neither OmpC nor OmpF, as reported previously (10). In contrast, the relative abundance of OmpD in the outer membrane does not change in response to changes in osmolarity, nor is it dependent on envZ function.…”
mentioning
confidence: 60%
“…The production of both OmpC and OmpF by serovar Typhimurium is dependent on envZ. A mutant derivative of LT2, SC2, with an envZ1005::Mud-P insertion makes neither OmpC nor OmpF, as reported previously (10). In contrast, the relative abundance of OmpD in the outer membrane does not change in response to changes in osmolarity, nor is it dependent on envZ function.…”
mentioning
confidence: 60%
“…This hypothesis is supported by the lack of complementation of the mutant strain ΔhrpG with the expression of the plasmid-encoded variant R210C. Similarly, a change of Arg to Cys at position 220 in a plasmid-encoded OmpR in a wild type background also exhibited dominance and it has been suggested that the loss of function phenotype may be caused by the interaction between wild-type and mutant polypeptides, the latter overproduced due to the multicopy state [ 29 ]. Moreover, Xcc-R210C could not elicit an HR in non-host plants, suggesting that even if a lower expression of hrp genes in this strain allows the T3SS assembly during host plants infection, it is not sufficient to elicit the rapid plant defense response that occurs during HR and in which the bacteria is not growing inside the non-host plant tissue [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that MH760 remains OmpC-even in the presence of increased amounts of the altered OmpR protein (25,33). Perhaps high expression of ompB in IHF mutants leads to changed levels of EnvZ in relation to OmpR.…”
Section: Methodsmentioning
confidence: 99%